Voice signal analysis techniques for cognitive decline (stress) assessment - Loizou, Christos P.; Christodoulides, Paul (My University, 2020)
Speech signals may provide important information for measuring and modelling human behaviour, especially for assessing mental health as well as estimating the emotional state of a person. Speaker’s physiological and/or physical state may be thus identified by detecting the cognitive decline (CD) or stress levels using signal analysis of voice. This preliminary study presents a survey on methods introduced for CD and stress voice detection in humans. It is shown that increase in signal’s fundamental frequency (f0) as well as its frequency formants, are the most common effects of CD and stress. Additional voice parameters could be used to identify normal from CD and normal from stressed voice as well as the cognitive state of the elderly. The present study poses the initiation of a project for the development of a mobile application for the automated voice detection and analysis on the fly, which will aid in the detection of early signs of CD and stress. Further investigation with application on a large number of voice samples is required for validating the methods.
A Brief Survey of Voice Signal Analysis Techniques for Cognitive Decline (Stress) Assessment
Keywords: Cognitive decline and stress voice analysis; Formant frequencies index; Voice analysis; Fundamental frequenc